Samuiṅʻʺ vaṅʻ khoṅʻʺ choṅʻ krīʺ myāʺ e* ṅāʹ nuiṅʻ ṅaṃ, ṅāʹ lū myuiʺ, ṅāʹ praññʻ thoṅʻ cu - ʼImʻ Mai Yañʻ ʼEʺ (Rvhe Pa ra puikʻ Cā pe : Praññʻ luṃʺ kyvatʻ phranʻʹ khyī reʺ, Paññāʻ Rhaṅʻ Cā pe, 1986)
Biographies of Burmese revolutionaries and nationalists in the history of Burma, 1826-1948.